Alternative Household Fuel: Fruitless Palm Based on Gasification Biomass with Gasoline and Liquefied Petroleum Gas - Saloko, Subakho Aryo; Nurcahyono, Nurcahyono; Kurniawan, Indra; Hartono, Hartono; Gunawan, Sri (Akademi Komunitas Perkebunan Yogyakarta, 2025)
Fuel sources derived from oil palm plants are abundant but have not been optimally utilized by the community. This study aims to show the performance efficiency of cheap fuel fruitless (Brondolan) using people's stoves as fuel substitutes for kerosene, coal, and Liquid Petroleum Gas (LPG). This study uses a quantitative observation method. The types of fuel and stove materials used include (1) conventional kerosene-fired stoves, (2) conventional LPG-fired stoves, (3) gasified biomass stoves fueled with palm fruit, (a) large stove size (Prime Brand), and (b) small stove size (People's Stove Brand). The research procedure is measured by heating 5 liters of water from room temperature to boiling (1000C). The results show that fruitless is more efficient than gasoline, coal, and LPG is more efficient. Based on trials, heat 5 liters of water to a boil at Rp. 200, Gasoline Rp. 1,650, and LPG Rp. 381. The government's role is to provide socialization and policies in applying alternative materials with lozenges to reduce the use of gasoline and LPG. Unrefined fuel can be an alternative material for household scale stoves.